The Evaluation Of The Toxic Effect Of And Its Paraquat Mechanism Of Action On Reproductive System Of Male Rats - Zain, Anuar Md. (2007)
Paraquat‘r") - PQ (1.1’ — dimethyl 4.4' - bipyridillium dichloride) is a nonselective contact herbicide. Its herbicidal and toxicological properties are dependent on the ability of the parent cation to undergo a single electron addition to form a free radical. The present study was conducted to evaluate the toxic effect of low dose of PO and its mechanism of action on the reproductive system of adult male rats. Two routes of administration were selected; oral and dermal which are the most common exposure routes in human being Groups of six male Sprague-Dawley rats (n=6) were orally gavaged in selected dose of 2mg/kg. 5mg/kg and 20mg/kg (1/80, 1/32 and 1/8 of oral LD50) and dermally applied in selected dose of 6mg/kg, 15mg/kg and 30mg/kg (1/15, 1/6. and 1/3 of dermal LD50) for five consecutive days separately and scheduled for 7, 28. 42, 84 and 105 days for oral, and 7, 14. 28 and 42 days for dermal applications in separate groups after the last dose, Body weight did not show any change in the treated groups compared to the control.